Applying of Scientific Approach on the Result of Learning Natural Science at State Elementary School 1 Segalamider Bandar Lampung - Nureva, Nureva; Melinda, Mella (CV. Creative Tugu Pena, 2022)
The main problem of this study was low learning outcomes of Natural Science that obtained by students at state elementary school 1 Segalamider Bandar Lampung. This artilcle analyzed the effect of the Scientific Approach on students' learning outcomes of natural science. The sample of this research was 27 students. The analysis used is the Hypothesis Test using the Dependent Sample T-test, namely Paired Sample T-test (Paired Sample T-Test). The results of this study indicated that the hypothesis testing results obtained by tcount> ttable, namely t account of 7,834 with t table of 2,056. With a significant level of 0.05 or 5%, which means that Ha is accepted and H0 is rejected. This means that the scientific approach has an effect on the learning outcomes of class V SD Negeri 1 Segalamider Bandar Lampung. Keywords: Scientific Approach, Learning Outcomes, Learning Natural Science